Characteristics of grocery and daily needs shopping in Greater Jakarta - Putranto, L.S. (IOP Publishing Ltd, 2020)
Grocery shopping is an important routine activity. 125 respondents, were interviewed in Greater Jakarta. The collected data were analysed using mean difference t-tests and Pearson correlation analyses. These were to obtain the factors affecting daily grocery shopping location and transport mode. We also would like to observe whether product price, available payment method and type of shops were affecting shopping location. We also want to know what convenience factors affecting shopping location and the characteristics of purchase products. In general, purchased product, shop opening hours, availability of shopping list, transport mode, shop distance from home or office, convenience level, other purchased products besides grocery and availability of restaurant nearby the shop were significantly affecting the choice of shopping location. Â© 2020 IOP Conference Series: Materials Science and Engineering.